Technology assessment: Dynamic electromyography in gait and motion analysis - Rechtien, J. J.; Gelblum, J. B.; Haig, A. J.; Gitter, A. J. (Muscle & Nerve, 1999)
Dynamic electromyographic measurements have been incorporated into studies of human gait, and in a broader sense, studies of human limb motion and even human torso motion, since the early 1950s. Initially, these measurements were purely investigational in nature, but the instrumented study of gait and motion has emerged as a clinical tool. Because of member interest in dynamic electromyography (EMG) in general, the American Association of Electrodiagnostic Medicine (AAEM) has undertaken a review of the literature in an effort to examine the clinical role of dynamic EMG measurements in gait and motion analysis. The papers cited below were viewed as representative of the literature on the subject in general and form a basis of the present document.